Terapia logopedyczna przez zabawę - Polczyk, Martyna (Logopedia Silesiana, 2015)
The purpose of the study is to present certain play which can be successfully applied to the speech therapy of children with the abnormal execution [š, ž, č, ǯ, r]. The speech therapy is conducted through fun. The form undertaken is to encourage children to do the exercises of speech therapy more frequently.